Flexible enzymatic activation of artificial polyketide extender units by Streptomyces cinnamonensis into the monensin biosynthetic pathway. (1st September 2018) - Möller, D.; Kushnir, S.; Grote, M.; Ismail‐Ali, A.; Koopmans, K.R.M.; Calo, F.; Heinrich, S.; Diehl, B.; Schulz, F.
Abstract: Streptomyces cinnamonensis A495 is a variant of the monensin producer which instead of the native polyether antibiotic gives rise to antibiotic and anti‐tumour shunt‐product premonensin. Through the supplementation of the fermentation medium with suitable precursors, premonensin can be derivatized via the incorporation of new‐to‐nature extender units into the biosynthetic machinery. Polyketide extender units require activation, typically in form of coenzyme A‐thioesters. These are membrane impermeable and thus in the past an artificial mimic was employed. Here, we show the use and preliminary characterization of a highly substrate promiscuous new enzyme for the endogenous thioester formation in a Streptomyces strain. These intracellularly activated alternative extender units are significantly better incorporated into premonensin than the synthetically activated counterparts. Significance and Impact of the Study: Polyketide natural products are of enormous relevance in medicine. The hit‐rate in finding active compounds for the potential treatment of various diseases among this substance family of microbial origin is high. However, most polyketides require derivatization to render them suitable for the application. Of relevance in this field is the incorporation of artificial substances into the biogenesis of polyketides, hampered by both the microbial metabolism and the complexity of the enzymes involved. This manuscript describes the straightforward and selective biosynthetic incorporation of synthetic substances into a reduced polyketide and showcases a promising new enzyme to aid this purpose.